2021
DOI: 10.1001/jamadermatol.2020.4324
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Laboratory, and Interferon-Alpha Response Characteristics of Patients With Chilblain-like Lesions During the COVID-19 Pandemic

Abstract: IMPORTANCE Chilblain-like lesions have been reported during the coronavirus 2019 (COVID-19) pandemic. The pathophysiology of such manifestations remains largely unknown. OBJECTIVE To perform a systematic clinical, histologic, and biologic assessment in a cohort of patients with chilblain-like lesions occurring during the COVID-19 pandemic. DESIGN, SETTING, AND PARTICIPANTS In this prospective case series carried out with a COVID-19 multidisciplinary consultation group at the University Hospital of Nice, France… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
144
1
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(160 citation statements)
references
References 15 publications
8
144
1
7
Order By: Relevance
“…They speculated that the direct infection of endothelial cells may be sufficient to induce local type I IFN induction and CLL. 7 This finding has been recently supported by Hubiche et al 6 , who demonstrated an increased IFN-alfa response in CLL patients as compared to non-CLL patients with acute COVID-19 infection. The hypothesis of a pathogenetic role of IFNs in the development of CLL is further supported by the observation that patients with chronic type I IFN activation due to rare genetic type I interferonopathies frequently develop chilblain lesions.…”
Section: Dear Editormentioning
confidence: 73%
“…They speculated that the direct infection of endothelial cells may be sufficient to induce local type I IFN induction and CLL. 7 This finding has been recently supported by Hubiche et al 6 , who demonstrated an increased IFN-alfa response in CLL patients as compared to non-CLL patients with acute COVID-19 infection. The hypothesis of a pathogenetic role of IFNs in the development of CLL is further supported by the observation that patients with chronic type I IFN activation due to rare genetic type I interferonopathies frequently develop chilblain lesions.…”
Section: Dear Editormentioning
confidence: 73%
“…Reports of delayed onset chilblain-like lesions predominantly affecting the lower extremities have increased during the pandemic, but strong conclusions about its etiology cannot be made due to inconsistent clinical and laboratory evidence of prior SARS-CoV-2 infection. While the younger age of these patients make asymptomatic or mild COVID-19 more likely, and may therefore reduce the sensitivity of SARS-CoV-2 testing, no study has proven a pathologic link between SARS-CoV-2 and chilblains [69]. Results of a recent study suggest that chilblains may be a manifestation of a post-viral type I interferonopathy [69].…”
Section: What Is the Relationship Between Autoimmunity And The Newly Defined Post Covid-19 Syndromes Such As Mis-c And Mis-a?mentioning
confidence: 99%
“…We did not perform correlation analyses with the number of COVID-19–related deaths. Indeed, chilblain-like lesions are associated with mild or asymptomatic SARS-CoV-2 infection [ 40 , 41 ], thus undermining correlation analyses with the number of COVID-19–related deaths, and correlations with the number of detected COVID-19 cases are unreliable owing to the limited number of tests performed at the beginning of the pandemic in many countries. Therefore, caution must be exercised when performing correlation analyses between GT data on chilblain-like symptoms and COVID-19 progression.…”
Section: Discussionmentioning
confidence: 99%